66.5k views
1 vote
Multiply using distributive property.

(2x-5)(4x2-3x+1)

PLEASE HELP!!! ASAP!!!

User Snakey
by
4.6k points

2 Answers

6 votes

Answer:

8x^3 - 26x^2 + 17x - 5.

Explanation:

(2x - 5)(4x^2 - 3x + 1)

= (2x * 4x^2) + (-5 * 4x^2) + (2x * -3x) + (-5 * -3x) + (2x * 1) + (-5 * 1)

= 8x^3 + (-20x^2) + (-6x^2) + 15x + 2x - 5

= 8x^3 - 26x^2 + 17x - 5.

Hope this helps!

User Rezzie
by
5.2k points
2 votes

Answer:

33x-6x(square)-45

Explanation:

(2x-5)(9-3x)

= 2x(9-3x) + -5(9-3x)

= 18x-6x(square) - 45+15x

= 33x-6x(square)-45

User Peter Boone
by
4.9k points